National Survey of DNA Crime Laboratories, 2001 ([Verlag nicht ermittelbar], 2003)
This study contains data from a survey of publicly operated forensic crime labs that perform deoxyribonucleic acid (DNA) testing. The survey was a follow-up to the initial survey of DNA crime labs in 1998 (ICPSR study 2879). The survey included questions about each lab's budget, personnel, procedures, equipment, and workloads in terms of known subject cases, unknown subject cases, and convicted offender DNA samples. The survey was sent to 135 forensic laboratories, and 124 responses were received from individual public laboratories and headquarters for statewide forensic crime laboratory systems. The responses included 110 publicly funded forensic laboratories that performed DNA testing in 47 states.